Trauerspiele mit Gesang und Tanz Zur Ästhetik und Dramaturgie jüdischer Theatertexte - Dalinger, Brigitte (2010)
From 1890 until 1938 in Vienna, Jewish theatre was a lively and fascinating part of the theatrical scene. Yiddish operettas and melodramas, serious plays and so-called Jargonschwänke were staged. The widespread texts of these Jewish theatre-evenings, in Yiddish and German, are discussed and analysed in this work.